Reconstruction of the Limits of Advocates' Immunity Rights in Assistance in Corruption Cases to Prevent Professional Abuse and Ensure Legal Certainty - Chitto Cumbhadrika; Zainal Arifin Hoesein (SULTAN ADAM: Jurnal Hukum dan Sosial, 2026)
This study aims to analyze the problematic regulation of advocate immunity rights in assisting corruption cases and formulate a reconstruction of the limits of advocate immunity rights based on legal certainty. The study uses a normative juridical method with a statutory and conceptual approach. The results of the study indicate that the regulation of advocate immunity rights, as regulated in Article 16 of Law Number 18 of 2003 concerning Advocates and Constitutional Court Decision Number 26/PUU-XI/2013, still contains unclear norms, particularly regarding the phrase "good faith" and the limits of professional actions that receive legal protection. This situation creates legal uncertainty and opens opportunities for abuse of the advocate profession in cases of corruption, including bribery, obstruction of justice, money laundering, concealment of assets obtained through corruption, and witness tampering. The proposed legal reconstruction involves formulating indicators of good faith, affirming the limits of the legal profession, adopting the concept of the crime-fraud exception, and amending Article 16 of the Advocates Law to emphasize that the right to immunity does not apply to actions taken by advocates to commit, assist, facilitate, or conceal corruption. This reconstruction aims to balance the independence of the legal profession with effective corruption eradication to ensure legal certainty, justice, and benefit.